Psychometric properties of the Belief about the Educational Process in the Rural Environment Scale (CAPE-R) in teachers from Mendoza, Argentina - Labin, Agustina (2018)
This study analyzes the psychometric structure of the CAPE- R scale, which assesses the beliefs about the educational process in rural teachers; explores the teacher´s profile, and analyzes the significant differences between the beliefs according to sociodemographic variables. The sample included 150 rural teachers from Mendoza, Argentina. The exploratory factor analysis yielded a factorial structure made up of four factors that explained a 44.19% of the variance of responses to the test. Internal consistency coefficients ranged from .74 to .85. The data show a predominance of difficulties in the educational process dimension (M=2.83; DE=.69), the only dimension that reached a significant association with the educational level of the classes (F =4.77, p<.05).